Climate governance, policy entrepreneurs and small states: explaining policy change at the International Maritime Organisation. Issue 5 (28th July 2020) - Corbett, Jack; Ruwet, Mélodie; Xu, Yi-Chong; Weller, Patrick
ABSTRACT: The Marshall Islands (RMI) is one of the world's smallest sovereign states, which should mean they are peripheral to global climate negotiations. Yet, they have recently played a crucial role in negotiating the Paris Agreement and emissions reductions at the International Maritime Organisation (IMO). The success at Paris is well documented. Here we explain how they also acted as successful policy entrepreneurs at the IMO. Specifically, we find that RMI's success can be explained by three factors: vision of the entrepreneur; development of capacity within RMI and the region, and commitment of key actors to create and seize opportunities in available forums, to realise that vision; and strategies to mobilise broader international support. These findings have implications for the literatures on policy entrepreneurship in climate governance and studies that highlight the capacity of small states to influence international affairs.